Perencanaan program ibu care posyandu turry melalui peer support group - Ramadani, Nurul Ma'rifa; Makmur, Nindha Aulia; Faradiana, Dwi Nur; Gustia, Wanda; Anggraeni, Diva Nabilah; Rahmayanti, Desy Anugerah; Rahayu, Agustin Putri; Permana, Lies; Rohmah, Nur; Nurrachmawati, Annisa; Feriyanti, Alma; Fikri, Mohammad (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Posyandu (Integrated Health Post) is a community-based health service that plays a crucial role in improving maternal and child health. However, at Posyandu Turry, there is still a lack of understanding and participation from mothers, which impacts the effectiveness of Posyandu services. Purpose: To identify problems at Posyandu Turry, prioritize problems using ultrasound methods, and plan an empowerment program that can increase community knowledge and participation in Posyandu activities on an ongoing basis. Method: This study identified problems at the Turry Integrated Health Post (Posyandu), determined priorities using the USG method, and developed an empowerment program using a qualitative case study approach and Participatory Action Research (PAR). Data were collected through interviews, focus group discussions (FGDs), observations, and document analysis. Results: The FGDs revealed that low community knowledge about the importance of Posyandu was the highest-scoring problem. This was due to limited access to information and a lack of engaging educational materials. Based on these findings, the